Platforms' regulatory disruptiveness and local regulatory outcomes in Europe - Eliska Drapalova; Kai Wegrich (Internet Policy Review, 2024)
One of the manifestations of platform power is the ability of platforms to successfully ignore existing rules and disrupt established patterns of regulation, thereby challenging the pillars of the regulatory state. But while the disruptive nature of the platform economy has often been invoked, it has rarely been empirically researched. We aim to fill this gap by putting the 'disruption' thesis to the test. We investigated whether platform companies disrupt local regulations. The findings show that sectoral platform companies are less disruptive to local regulations than widely believed. Platforms face a variety of regulatory responses, including the enforcement of regulations and the banning of platforms that fail to respect local rules. We operationalise disruption as the implementation of new regulation, exploring where and whether regulatory disruption takes place. This article combines a comparative analysis of 99 city regulations in the transport (ride-hailing) and housing (apartment-sharing) sectors in which platform companies are active, with examples from qualitative case studies.
Keywords: 300; Platform power; Disruption; Platform regulation; Regulatory disruption; Cities